The netter collection of medical illustrations : muscuoskeletal system, volume 6 - Iannotti, Joseph P.; Parker, Richard D. (Netter green book collection, 2013)
A guide to the musculoskeletal system that covers topics ranging from basic science and anatomy to orthopaedics and rheumatology. It offers insights into musculoskeletal anatomy, physiology, and clinical conditions.